Investigation of the Pulsed Annular Gas Jet for Chemical Reactor Cleaning - Zvegintsev Valery Ivanovich; Nalivaichenko Denis Gennadievich; Chirkashenko Vladimir Fedorovich (International Journal of Chemical Engineering)
The most economical technology for production of titanium dioxide pigment is plasma-chemical syntheses with the heating of the oxygen. The highlight of the given reaction is formation of a solid phase as a result of interactions between two gases, thus brings the formation of particle deposits on the reactor walls, and to disturbing the normal operation of the technological process. For the solving of the task of reactor internal walls cleaning the pulsed gaseous system was suggested and investigated, which throws circular oxygen jet along surfaces through regular intervals. Study of aerodynamic efficiency of the impulse system was carried by numerical modeling and experimentally with the help of a specially created experimental facility. The distribution of the pulsed flow velocity at the exit of cylindrical reactor was measured. The experimental results have shown that used impulse device creates a pulsed jet with high value of the specified flow rate. It allows to get high velocities that are sufficient for the particle deposits destruction and their removal away. Designed pulsed peelings system has shown high efficiency and reliability in functioning that allows us to recommend it for wide spreading in chemical industry.